A study on factors contributing student’s interest to be an insurance agents / Mohamad Azri Mohd Azmi and Siti Noraliza Mohd Rohaizai - Mohd Azmi, Mohamad Azri; Mohd Rohaizai, Siti Noraliza (Faculty of Business and Management, 2016)
Insurance agents are a critical insurance activity that contributes for a major portion of the revenue generation for Insurance or Takaful Company. The purpose of this study was to examine factors that contributing student's interest to be an insurance agent. Male and female undergraduate students in Universiti Teknologi MARA (UiTM) which study in insurance course were surveyed through a structural questionnaire to determine their interest in insurance agent's career. The scope of study will be focusing on the insurance students of UiTM Kampus Bandar Melaka and UiTM Puncak Alam. The researchers choose UiTM Kampus Bandar Melaka and UiTM Puncak Alam to do research because many insurance students are located in both of UiTM branches. The researcher using questionnaire to attained the data in order to get the feedback. In this study, researcher was using Statistical Package for Social Sciences (SPSS) technique. Based on reliability test, respondent demographic and multiple regressions, a clear findings and result is observed. The researchers provide some recommendations and suggestion for future research. The conclusion of this study was the outcome from the survey analysis and findings.